Use of ureteral catheter in uterine-sparing surgery for placenta accreta - Şükran Doğru; Aslı Altınordu Atcı; Fatih Akkuş; Gülnur Eren; Ali Acar (Perinatal Medicine Foundation, 2022)
Objective: The study aimed to investigate the effect of ureteral catheter use during surgery on the outcomes of obstetric and urinary complications in patients with placenta accreta spectrum (PAS) and placenta previa. Methods: The patients who were followed up at Meram Medical Faculty Hospital of Necmettin Erbakan University between January 2016 and November 2021 and diagnosed with PAS and placenta previa were included. Patients who underwent emergency and planned surgery were grouped as those with or without an intraoperative ureteral catheter. The primary outcome was determined as the rate of urinary system damage among these groups. The number of blood transfusions, preoperative and postoperative hemoglobin values and hemoglobin changes, length of hospitalization, patients who underwent uterine-sparing surgery or hysterectomy, urinary tract injury, and wound infection were compared regarding the use of catheters. Results: A total of 122 patients were included in the study. While an intraoperative ureteral catheter was placed in 56 (45.01%) patients, it was not used in 66 (54.09%) patients. Bladder injuries were determined in 31 (55.4%) patients with a catheter and 13 (19.7%) patients without a catheter, and no other urinary system injuries were found. The incidence of bladder injury was statistically significantly higher in the group with a catheter (p=0.001). The number of transfused erythrocyte suspensions, the hemoglobin change according to the preoperative hemoglobin level, and the mean duration of hospitalization in patients with a catheter were statistically significantly greater than the group without a catheter (p=0.001). Conclusion: Ureteral catheterization did not reduce urinary damage in patients with PAS and placenta previa who underwent uterine-sparing surgery and hysterectomy. However, we believe that the insertion of a catheter increases the possibility of diagnosing intraoperative damage.